Linguistic incompetence in English-Arabic translation: a case study of "prepositions" among Arabic students in The Federal College Of Education (technical) Gusau, Zamfara State, Nigeria - Ahmad, Aliyu; Syed Abdullah, Syed Nurulakla; Mustapha, Nik Farhan; Toklubok@Hajimaming, Pabiyah; Yaakob, Nor Azuwan; Ridzwan, Zaharom (ASR Research India, 2022)
Previous studies have shown that the process of translation from English to Arabic involves many obstacles, especially those related to linguistic elements. This makes it even more complicated for tertiary students and has led the researchers to examine some common errors in translating prepositions from English into Arabic and to uncover the causes of linguistic difficulties in translating prepositions from English into Arabic. As a case study, the researchers used a qualitative approach by employing an assessment tool and conducting interviews with the study sample group. After analysing the data collected, the researchers found some errors that Arabic students encounter, including addition, subtraction and omission according to the theory of translation error detection (Sager, 1983). The survey conducted later revealed four reasons for these difficulties, including differences between prepositions in English and Arabic, prepositions are more complicated in English, they duplicate Arabic and there are no set rules for the use of prepositions in English. Some suggestions were also made to solve these difficulties. Finally, this study is of great importance to Arabic students, scholars and English-Arabic translators as it provides them with an awareness of common errors in English-Arabic translation.